China Shifts Gears in New Effort to Foster Universities - Zha, Qiang (International Higher Education, 2025)
The Chinese government recently launched a number of initiatives focused on improving university teaching and learning outcomes. They aim at cultivating high-caliber talent independently, which is crucial for China’s long-term goal of national development. Such initiatives, however, are not without challenges and pitfalls.